SISTEM INFORMASI INVENTARIS ASET PADA DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI JAMBI: Information Systems,Asset,Inventory,UML,Prototype - Yeniwati, Desi (LP2M Universitas Nurdin Hamzah, 2019)
The Jambi Province Communication and Information Office is included in the organizational structure of the Jambi Province Regional Secretariat. Asset management at the Jambi Provincial Communication and Information Office is done manually and using Microsoft office excel so that the performance of the asset management system is still not optimal. One way that management can be optimized is by the use of information systems. This asset research is carried out at the asset planning, asset procurement, and asset receipt stages. This research resulted in a prototype system that described the functional planning, procurement, and receipt of assets at the Provincial Communication and Information Office. The method used is an object-oriented approach using PHP & MySql programming to accommodate the database of the application. The result of this final project is an Asset Inventory Information system that will facilitate the administration of office assets.